Preliminary study of servant songs of Isaiah and “integration of heaven and human” of traditional Chinese thought - WANG, Dong (Journal of Research for Christianity in China (JRCC), 2025)
“Integration of heaven and human” is an important topic of Chinese philosophy, this paper will discuss the idea of Integration of heaven and human in Zhang zai’s work Ximing . Based on his discussion of the Integration of heaven and human through his cosmic understanding, he discussed his understanding of social ethic and personal ethic of life and death, opinion of wealth, is an portrait of traditional Chinese Confucian intellectual. There is similarity with the emergence of servant songs of Isaiah, they all face the same public issues, however, there is different response regarding their ways of handling the public issues.
Keywords: Integration of heaven and human, Ximing, Servant Songs, Creation